Discriminative ability of the three functional tests in independent ambulatory patients with spinal cord injury who walked with and without ambulatory assistive devices - Saensook, Wilairat; Poncumhak, Puttipong; Saengsuwan, Jiamjit; Mato, Lugkana; Kamruecha, Worawan; Amatachaya, Sugalya (The journal of spinal cord medicine, 2014)
Background/objectives Many persons with spinal cord injury (SCI) require an ambulatory assistive device (AAD). An effective monitoring method enables the use of an appropriate AAD and promotes levels of independence for patients. This study investigated the discriminative ability of the three-functional tools relating to walking ability, including the 10-meter walk test (10MWT), the five times sit-to-stand test (FTSST), and the timed up and go test (TUGT), in independent ambulatory persons with SCI who walked with walker, crutches, cane, and non-AAD. Methods Eighty-five persons with SCI who could perform sit-to-stand and walk independently at least 50 m were cross-sectionally assessed for their functional ability using the 10MWT, FTSST, and TUGT. Results The findings for persons not using AADs were significantly better than the other groups for every test (P < 0.001). In addition, persons who walked with cane were significantly different from those who used walkers (P < 0.001) but there were no significant differences between persons who used walker and crutches for every test (P > 0.05). Conclusion The findings supported the discriminative validity of the tools, allowing them to indicate functional changes in persons with SCI who walk with different AADs. However, the non-significant differences between subjects who used a walker and crutches may relate to the method of subject arrangement and inclusion criteria that recruit subjects with rather good walking capability and lower limb function. The findings may also suggest the use of the sit-to-stand maneuver as a simple screening tool for walking advancement of walker users, pending further investigation.